The Effect of Room Price on Occupancy at Kenari Hotel - Wayan Suardana; Aris Baharuddin; Muhadjir Suni (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Kenari Hotel at Parepare Regency needs to carry out a strategy in the quality of service, service, and hotel room sales rates. This study aims to determine the Effect of Room Prices on Occupancy at Kenari Hotel at Parepare Regency. The type of research used in this research is quantitative research. Based on the results of the study regarding the independent variable or free variable room prices and the dependent variable that is the occupancy rate. A coefficient of 34% and the remaining 66% is needed by other factors namely, service quality, customer satisfaction, promotions and so on that are not by this study. meaning that each increase in room price variable (x) by one percent will increase room occupancy at Kenari Hotel at Parepare Regency amounting to 0.238. Meanwhile, determining a coefficient of 34% and the remaining 66% is needed by other factors. Meaning that each increase in room price variable (x) by one percent will increase room occupancy at Kenari Hotel at Parepare Regency amounting to 0.238. This research can be used as a reference in developing the level of tourism in Indonesia, especially in the hotel sector.